Hubungan Jamuan Makan dan Beban Simbolik Pada Ibadah Rumah - Doloy, Agrilivita; Frans, Edison; Pohan, Juan Erwin (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2025)
This study explores church members’ participation in household worship, particularly the relationship between economic conditions and social customs surrounding hospitality practices. The research was conducted at Syalom Kantaman Congregation in Banggai Kepulauan, Central Sulawesi. The study aims to examine whether economic conditions influence members’ readiness to host home worship services and whether the habit of providing meals acts as a moderating factor. A quantitative method with a survey approach was employed. The sample consisted of 30 purposively selected active church members. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression and moderation analysis via SPSS. The findings show that economic conditions do not significantly affect members’ readiness. However, when the habit of providing meals is included as a moderating variable, the influence of economic conditions becomes statistically more apparent. The study concludes that social pressure stemming from hospitality norms plays a more substantial role than economic realities in shaping participation. These findings highlight the need for more contextual and liberating pastoral and liturgical approaches.